2010
DOI: 10.1158/1078-0432.ccr-09-1840
|View full text |Cite
|
Sign up to set email alerts
|

MiR-222 Overexpression Confers Cell Migratory Advantages in Hepatocellular Carcinoma through Enhancing AKT Signaling

Abstract: Purpose: This study aims to profile the expressions of 156 microRNAs (miRNA) in hepatocellular carcinoma (HCC) and to characterize the functions of miR-222, the most significantly upregulated candidate identified.Experimental Design: miRNA expression profile in HCC tumors, matching adjacent cirrhotic livers, and cell lines was conducted using quantitative PCR. Common miR-222 upregulations were further validated in a larger cohort of tumors. The functional effects of miR-222 inhibition on HCC cell lines were ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(187 citation statements)
references
References 34 publications
9
174
2
2
Order By: Relevance
“…Paradoxically, miR-222 was previously regarded as oncogene in some reports because it could enhance some tumour cell growth by targeting CDK inhibitor p27 in vitro, and was found to be upregulated in HCC and some other types of cancers 42,51,52 ; however, its tumourpromoting role was rarely validated in vivo. Our data support miR-222 to be a tumour suppressor in HCC by controlling the stemness and tumorigenicity of a2d1 þ TICs, further confirming that the roles of miRNAs are cell context-dependent 50 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, miR-222 was previously regarded as oncogene in some reports because it could enhance some tumour cell growth by targeting CDK inhibitor p27 in vitro, and was found to be upregulated in HCC and some other types of cancers 42,51,52 ; however, its tumourpromoting role was rarely validated in vivo. Our data support miR-222 to be a tumour suppressor in HCC by controlling the stemness and tumorigenicity of a2d1 þ TICs, further confirming that the roles of miRNAs are cell context-dependent 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the downregulation of let-7c and miR-200b and the upregulation of miR-222 were found extensively in HCC cells [40][41][42] , the fact that most HCC cells remain a2d1-negative led us to propose that miR-222 could rescue the effects of let-7c/miR-200b down-regulation on the expression of PBX3 and a2d1 in HCC cells. To test this hypothesis, we overexpressed miR-222 in Huh7 cells with let-7c and miR-200b knocked down simultaneously by respective Tud RNAs.…”
Section: Mir-222 Overcomes the Effects Of Let-7c/mir-200b Knockdownmentioning
confidence: 99%
“…This effect confers a metastatic potential in cancer cells as demonstrated by Wong et al (2010). Yang et al (2014b) suggested that MiR-222 overexpression promotes proliferation of human HCC cells by downregulating the p27 expression at post-transcriptional level.…”
Section: Mir-222mentioning
confidence: 95%
“…A recent discovery of PTEN is that microRNA-221 and microRNA-222 directly target genes involved in TRAIL resistance and increase the mobility of HCC [27]. In addition to the PTEN gene, microRNA-221 and microRNA-222 can also directly regulate protein phosphates' 2A subunit B (PPP2R2A) and tumor suppression factor TIMP3 expression, thereby activating the Akt signaling pathway and metal epitope peptide to promote the invasion and metastasis of HCC [28]. A report also shows a new microRNA (microRNA-143) mediated nuclear factor kb (NF-κB), promotes hepatitis B virus-related hepatocellular carcinoma metastasis [29].…”
Section: Micrornas and Metastasis Of Hccmentioning
confidence: 99%